Degradation Of Soil Properties Under Ginger, Turmeric, Aroid, And Jhum Rice Cultivation In Hilly Areas Of Bangladesh (Bangladesh Journal of Agricultural Research, 2013)
An experiment was conducted in Hill Agricultural Research Station (HARS), Khagrachari during 2011-2012 to estimate the soil loss and changes in soil properties under indigenous cultivation methods of ginger, turmeric, aroid, and jhum rice in hill slopes. The use of indigenous cultivation methods for growing different crops has created negative impact on soil productivity in hill slope. Among the four crops, the annually highest soil loss (22.68 t/ha) occurred by ginger cultivation which was statistically similar with turmeric (16.52 t/ha) followed by aroid (12.02 t/ha) and lowest soil loss (7.92 t/ha) occurred by jhum rice cultivation. There were no significant changes in soil physical properties like soil texture, bulk density, soil moisture content, field capacity. Organic matter and all the nutrients were higher in eroded soil than the post-harvested soil. A considerable amount of organic matter along with macro and micronutrients has been depleted through traditional method of crop cultivation. Bangladesh J. Agril. Res. 38(2): 363-371, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15897